Knowledge and competitive advantage : the coevolution of firms, technology, and national institutions - Murmann, Johann Peter, 1967- (Cambridge studies in the emergence of global enterprise., 2003)
A comparison of the development of the synthetic dye industry in Great Britain, Germany, and the US. The rise of this industry constitutes an important chapter in business, economic, and technological history because synthetic dyes - invented in 1857 -represent the first time that a scientific discovery quickly gave rise to a new industry. British firms led the industry for the next eight years, but German firms came to dominate the industry for decades before WWI, while American firms played only a minor role during the entire period. This study identifies differences in educational institutions and patent laws as the key reasons for German leadership in this industry. Successful firms had strong ties to the centers of organic chemistry knowledge. The book also argues that a complex coevolutionary process linking firms, technology and national institutions resulted in very different degrees of industrial success for dye firms in the three countries.